2016
DOI: 10.1158/0008-5472.can-15-2840
|View full text |Cite
|
Sign up to set email alerts
|

IL6 Blockade Reprograms the Lung Tumor Microenvironment to Limit the Development and Progression of K-ras–Mutant Lung Cancer

Abstract: Activating mutations of K-ras are the most common oncogenic alterations found in lung cancer. Unfortunately, attempts to target K-ras mutant lung tumors have thus far failed, clearly indicating the need for new approaches in patients with this molecular profile. We have previously shown NF-κB activation, release of IL-6, and activation of its responsive transcription factor STAT3 in K-ras mutant lung tumors, which was further amplified by the tumor enhancing effect of chronic obstructive pulmonary disease (COP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
173
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 55 publications
5
173
1
1
Order By: Relevance
“…We have previously found that the CM from TOV21G cells accelerates autophagy in other cells and have largely attributed this effect to their secretion of IL‐6 . TOV21G cells are known to have an activating KRAS mutation, and this has been shown to be important for IL‐6 production, especially in murine lung cancer models . We therefore wanted to establish whether activated KRAS was a major contributor to the IL‐6 production in our model system.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously found that the CM from TOV21G cells accelerates autophagy in other cells and have largely attributed this effect to their secretion of IL‐6 . TOV21G cells are known to have an activating KRAS mutation, and this has been shown to be important for IL‐6 production, especially in murine lung cancer models . We therefore wanted to establish whether activated KRAS was a major contributor to the IL‐6 production in our model system.…”
Section: Resultsmentioning
confidence: 99%
“…All of these findings suggest that IL-6 might be a crucial potential therapeutic target in lung cancer. Actually, Caetano et al found that anti-IL-6 treatment could be an alternative therapeutic strategy in lung cancer [76]. Interestingly the reaction of patients with NSCLC to analgesics could be predicted by detecting a gene polymorphism of IL-6, which has shown significant value in improving the quality of life and prognosis of such patients [77].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported activation of the JAK/STAT pathway in sex-determining region Y box 2 (SOX2)-driven, LKB1-deficient mouse model of squamous cell lung cancer (47) and increase of IL-6 production and subsequent activation of STAT3 in LKB1-deficient mouse model of LADC (48,49). As IL-6/JAK/STAT signaling axis plays important roles in cell proliferation, survival, invasion, chemoresistance, and immunosuppression, (48,(50)(51)(52)(53), targeting CPS1 might alter tumor microenvironment and improve efficiency of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%